Studi Komparasi Hasil Foto Dan Video Antara Mirrorless Camera Dan Iphone - Deli Deli; Inezhya Mayang Kirana Putri Sofiandi (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
As technology such as digital camera advances, now the mirrorless camera is already invented, where this device is much lighter and easier to use compared to the DSLR. However, in this digital age, cameras can now be attached to other equipments, most notably cell phones and since people are almost never separated from cell phones, mirrorless cameras may start falling behind. This research will determine the differences between the iPhone and mirrorless camera. It will also try to determine which type of camera the public prefer.